Involvement of eNAMPT/TLR4 inflammatory signaling in progression of non‐alcoholic fatty liver disease, steatohepatitis, and fibrosis - Sun, Belinda L.; Sun, Xiaoguang; Kempf, Carrie L.; Song, Jin H.; Casanova, Nancy G.; Camp, Sara M.; Reyes Hernon, Vivian; Fallon, Michael; Bime, Christian; Martin, Diego R.; Travelli, Cristina; Zhang, Donna D.; et al. (The FASEB journal, 2023)
Although the progression of non‐alcoholic fatty liver disease (NAFLD) from steatosis to steatohepatitis (NASH) and cirrhosis remains poorly understood, a critical role for dysregulated innate immunity has emerged. We examined the utility of ALT‐100, a monoclonal antibody (mAb), in reducing NAFLD severity and progression to NASH/hepatic fibrosis. ALT‐100 neutralizes eNAMPT (extracellular nicotinamide phosphoribosyltransferase), a novel damage‐associated molecular pattern protein (DAMP) and Toll‐like receptor 4 (TLR4) ligand. Histologic and biochemical markers were measured in liver tissues and plasma from human NAFLD subjects and NAFLD mice (streptozotocin/high‐fat diet—STZ/HFD, 12 weeks). Human NAFLD subjects (n = 5) exhibited significantly increased NAMPT hepatic expression and significantly elevated plasma levels of eNAMPT, IL‐6, Ang‐2, and IL‐1RA compared to healthy controls, with IL‐6 and Ang‐2 levels significantly increased in NASH non‐survivors. Untreated STZ/HFD‐exposed mice displayed significant increases in NAFLD activity scores, liver triglycerides, NAMPT hepatic expression, plasma cytokine levels (eNAMPT, IL‐6, and TNFα), and histologic evidence of hepatocyte ballooning and hepatic fibrosis. Mice receiving the eNAMPT‐neutralizing ALT‐100 mAb (0.4 mg/kg/week, IP, weeks 9 to 12) exhibited marked attenuation of each index of NASH progression/severity. Thus, activation of the eNAMPT/TLR4 inflammatory pathway contributes to NAFLD severity and NASH/hepatic fibrosis. ALT‐100 is potentially an effective therapeutic approach to address this unmet NAFLD need. NAMPT expression is significantly elevated in hepatic tissues from NAFLD patients and mice exposed to STZ/HFD‐induced NAFLD. eNAMPT neutralization with the humanized ALT‐100 mAb significantly reduced NAFLD severity and hepatic fibrosis in STZ/HFD mice. Our study supports eNAMPT/TLR4 signaling as a clinically relevant, highly druggable target with an eNAMPT‐neutralizing biologic therapeutic strategy to reduce the progression from steatosis to NASH and the development of hepatic fibrosis.